2011
DOI: 10.1016/j.jdent.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection procedures: Their efficacy and effect on dimensional accuracy and surface quality of an irreversible hydrocolloid impression material

Abstract: Please cite this article as: Rentzia A, Coleman DC, O'Donnell MJ, Dowling AH, O'Sullivan M, Disinfection procedures: their efficacy and effect on dimensional accuracy and surface quality of an irreversible hydrocolloid impression material, Journal of Dentistry (2010Dentistry ( ), doi:10.1016Dentistry ( /j.jdent.2010 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 28 publications
1
66
0
7
Order By: Relevance
“…As agar impression materials appear to require an immersion time of less than 10 min, agar-alginate combined impressions might have a similar requirement. The germicidal effects of short-term immersion of hydrocolloid impression materials in disinfectant solutions have been reported 12,15,16) . Therefore the aim of this study was to examine the effects of immersion of agar-alginate combined impressions in disinfectant solutions for 1, 3, 5 and 10 min on the surface properties of the resulting stone casts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As agar impression materials appear to require an immersion time of less than 10 min, agar-alginate combined impressions might have a similar requirement. The germicidal effects of short-term immersion of hydrocolloid impression materials in disinfectant solutions have been reported 12,15,16) . Therefore the aim of this study was to examine the effects of immersion of agar-alginate combined impressions in disinfectant solutions for 1, 3, 5 and 10 min on the surface properties of the resulting stone casts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that immersion of alginate impressions in 0.5% sodium hypochlorite solution for 1 min inactivates viruses 15) , and that immersion of alginate impressions in 0.6% sodium hypochlorite solution for two min is sufficient to prevent bacterial growth 16) . Complete elimination of Pseudomonas aeruginosa colonies from alginate discs after immersion for 30 s in 0.55% ortho-phthalaldehyde solution or 120 s in 0.5% sodium hypochlorite solution has been reported 12) . Therefore, as a new infection control method for dental treatment, it may be necessary to examine the effects of short-term immersion of agar-alginate combined impressions in disinfectant solutions on the resulting stone casts.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Alguns métodos têm sido propostos para descontaminar os modelos de gesso, tais como imersão em solução de hipoclorito de sódio a 0,525% 11 ou incorporação de soluções desinfetantes no ato da mistura do gesso 25 . No entanto, esses métodos têm resultado em alterações nas propriedades dos gessos, tais como menor resistência à compressão e menor dureza superficial [26][27][28] .…”
Section: Discussionunclassified
“…This study has elucidated some of the consequences of increasing the time of contact between alginate and gypsum, however, this factor must be tested under other conditions to simulate the clinical routine, for example, performing disinfection of the casts, 18,19 as well as using 100% humidity while the plaster undergoes setting to avoid alginate syneresis. Further research is also suggested using other times of contact between alginate and plaster, longer than 1 hour, but shorter than 12 hours.…”
Section: Discussionmentioning
confidence: 99%